'An Arena of Glorious Work': The Protection of the Rural Landscape Against the Demands of Britain's Second World War Effort. Issue 2 (10th September 2018) - WILLIS, GARY
Abstract: This article explores the development of the Council for the Preservation of Rural England's (CPRE) policy response to the increasing demands for rural land by the armed forces and other war effort-related government departments prior to and during the Second World War. The CPRE was supportive of Britain's war effort, but nevertheless throughout the war sought to remain an effective advocate for the preservation of the rural landscape – a landscape that was regularly evoked by state propaganda to stimulate the population's support for the war effort, yet was subject to alteration and degradation by that very effort. The result was a generally private campaign of lobbying characterised by opposition to some war effort-related proposals for rural land use, acquiescence to others, and consistent efforts to seek to ensure that requisitioned land was returned to its prewar use. Central to the CPRE's capacity to influence was a consultative mechanism created by Prime Minister Neville Chamberlain in 1938, which established the CPRE as a stakeholder that government ministries were required to consult with over their proposed use of land in rural areas for airfields, training camps, war industry, and other purposes. The immediate postwar legacy of this work, both for the CPRE and the rural landscape, is also examined. This article therefore contributes, albeit from a tangential perspective, to the growing historiography on the militarisation of landscapes, defined by Coates et al. as 'sites that have been fully or partially mobilised for military purposes'. 2